2019
DOI: 10.1371/journal.pone.0213140
|View full text |Cite
|
Sign up to set email alerts
|

Skin conductance responses in Major Depressive Disorder (MDD) under mental arithmetic stress

Abstract: Depressive symptoms are related to abnormalities in the autonomic nervous system (ANS), and physiological signals that can be used to measure and evaluate such abnormalities have previously been used as indicators for diagnosing mental disorder, such as major depressive disorder (MDD). In this study, we investigate the feasibility of developing an objective measure of depressive symptoms that is based on examining physiological abnormalities in individuals when they are experiencing mental stress. To perform t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…On the other hand, biofeedback relaxation has been found to be associated with increases in peripheral skin temperature [41]. Electrical skin conductance values increase with sympathetic neutrally mediated palmar sweating [37]; multiple investigations have shown that acute mental stress is associated with increases in electrical skin conductance values [42][43][44][45][46]. Evidence in the literature shows that decreased BIS values are associated with decreased skin conductance [47].…”
Section: Effects Of Stress-relaxation On Other Autonomic Physiologymentioning
confidence: 99%
“…On the other hand, biofeedback relaxation has been found to be associated with increases in peripheral skin temperature [41]. Electrical skin conductance values increase with sympathetic neutrally mediated palmar sweating [37]; multiple investigations have shown that acute mental stress is associated with increases in electrical skin conductance values [42][43][44][45][46]. Evidence in the literature shows that decreased BIS values are associated with decreased skin conductance [47].…”
Section: Effects Of Stress-relaxation On Other Autonomic Physiologymentioning
confidence: 99%
“…However, the distinction between reactive aggression and proactive regression is important: reactive aggression is related to exaggerated SCL reactivity, but proactive aggression is associated with low SCL reactivity (Armstrong et al, 2019). In one of the few studies that has examined trajectories of SCL during a task rather than only averaging SCL, depressed adults exhibited lower mean SCL and lower increases in SCL while working on difficult mathematic problems compared to matched controls (Kim et al, 2019). In sum, anxiety and reactive aggression are related to exaggerated SCL reactivity, whereas depression and proactive aggression are related to low SCL reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the wearable device can provide the physiological data (i.e., HRV and SC) to complement the data from the smartphone, which are limited only to the behavior (i.e., acceleration and GPS) and social interaction (i.e., call and SMS) of the participants. Among various physical health data from the wearable devices, SC and HRV were scientifically proven to be related to mental health problems [32], [34], [35], [104]. The SC response of the patients with depression has been shown to be lower than that of the persons with strong mental health [104].…”
Section: Smartwatch Toward Psychological Supportsmentioning
confidence: 99%
“…Among various physical health data from the wearable devices, SC and HRV were scientifically proven to be related to mental health problems [32], [34], [35], [104]. The SC response of the patients with depression has been shown to be lower than that of the persons with strong mental health [104]. Additionally, patients with stress and anxiety symptoms were found to display lower HRV than that of the control group [32], [35].…”
Section: Smartwatch Toward Psychological Supportsmentioning
confidence: 99%